2014
DOI: 10.1038/leu.2014.106
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor activity of lenalidomide with the BET bromodomain inhibitor CPI203 in bortezomib-resistant mantle cell lymphoma

Abstract: Bortezomib therapy has shown promising clinical activity in mantle cell lymphoma (MCL), but the development of resistance to proteasome inhibition may limit its efficacy. To unravel the factors involved in the acquisition of bortezomib resistance in vivo, immunodeficient mice were engrafted with a set of MCL cell lines with different levels of sensitivity to the drug, followed by gene expression profiling of the tumors and functional validation of the identified gene signatures. We observed an increased tumori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 39 publications
6
79
2
Order By: Relevance
“…The mTOR is central to a signaling cascade leading to cell growth and proliferation, and mTOR inhibitors are approved for treatment of relapsed MCL (45). OTX015 was also synergistic with the PI3K-delta inhibitor idelalisib, which has shown promising clinical responses in B-cell lymphomas (46), and with the lenalidomide, as also recently reported for another BET bromodomain inhibitor in MCL (47).…”
Section: Discussionmentioning
confidence: 87%
“…The mTOR is central to a signaling cascade leading to cell growth and proliferation, and mTOR inhibitors are approved for treatment of relapsed MCL (45). OTX015 was also synergistic with the PI3K-delta inhibitor idelalisib, which has shown promising clinical responses in B-cell lymphomas (46), and with the lenalidomide, as also recently reported for another BET bromodomain inhibitor in MCL (47).…”
Section: Discussionmentioning
confidence: 87%
“…CPI203 was shown to have a synergistic effect with lenalidomide in bortezomib-resistant mantle cell lymphoma (MCL), both in vitro in cell lines and in a xenograft model [Moros et al 2014]. Plasmacytic differentiation, driven by IRF4 overexpression, has been linked to bortezomib resistance in MCL [Perez-Galan et al 2011], while MYC is a direct IRF4 target in activated B cells and myeloma [Shaffer et al 2008].…”
Section: Lymphomamentioning
confidence: 99%
“…CPI-203 is another benzodiazepine inhibitor structurally similar to JQ1, but with improved bioavailability profile in mice [King et al 2013]. It has shown preclinical evidence of efficacy in lymphomas [Ceribelli et al 2014;Moros et al 2014].…”
Section: The Development Of the Bet Proteins Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Some studies reported that lenalidomide has modest (pre)-clinical activity in lymphoma and AML with manageable toxicity. 9,12,13 Ongoing Phase I clinical trials assaying low- and high-dose lenalidomide for both newly diagnosed and relapsed/refractory AML also support that lenalidomide displays modest activity when given either alone or combined with cytarabine and anthracyclines. 14 …”
Section: Introductionmentioning
confidence: 96%